BmCPV-Derived Circular DNA vcDNA-S7 Mediated by Bombyx mori Reverse Transcriptase (RT) Regulates BmCPV Infection - Zhu, Min; Pan, Jun; Tong, Xinyu; Qiu, Qunnan; Zhang, Xing; Zhang, Yaxin; Sun, Sufei; Feng, Yongjie; Xue, Renyu; Cao, Guangli; Hu, Xiaolong; Gong, Chengliang (Frontiers in Immunology, 2022)
Circular DNAs derived from single-stranded RNA viruses play important roles in counteracting viral infection. However, whether double-stranded RNA viruses generate functional circular DNAs is still unknown. Using circDNA sequencing, divergent PCR, DNA in situ hybridization and rolling circular amplification, we presently confirmed that in silkworm, Bombyx mori cytoplasmic polyhedrosis virus (BmCPV), a double-stranded RNA virus belonging to cypovirus, is prone to produce a BmCPV-derived circular DNA termed as vcDNA-S7. We have also found that vcDNA-S7 formation is mediated by endogenous reverse transcriptase (RT), and the proliferation of BmCPV can be inhibited by vcDNA-S7 in vitro and in vivo. Moreover, we have discovered that the silkworm RNAi immune pathway is activated by vcDNA-S7, while viral small interfering RNAs (vsiRNAs) derived from transcribed RNA by vcDNA-S7 can be detected by small RNA deep sequencing. These results suggest that BmCPV-derived vcDNA-S7, mediated by RT, can serve as a template for the biogenesis of antiviral siRNAs, which may lead to the repression of BmCPV infection. To our knowledge, this is the first demonstration that a circular DNA, produced by double stranded RNA viruses, is capable of regulating virus infection.